Presoaking of Peroneus Longus Tendon Auto-graft in Vancomycin Decreases the Occurrence of Infection Following Arthoscopic Primary Anterior Cruciate Ligament Reconstruction: Presoaking of Peroneus Longus Tendon Auto-graft in Vancomycin - Saud, Abdul Munaf; Rashid, Muhammad; Raza, Tauseef; Napar, Abdul Rasheed; Khan, Naveed; Abidi, Syed Abdur Rub (Pakistan Journal of Health Sciences, 2025)
Septic arthritis following anterior cruciate ligament (ACL) repair surgery is an extremely rare but possibly fatal consequence. To mitigate this danger, our team began presoaking grafts with vancomycin. Objectives: To determine the association of septic arthritis following anterior cruciate ligament (ACL) restoration using hamstring autografts with and without grafts presoaked in vancomycin. Methods: This study included 350 patients who had primary hamstring autograft ACL repair. Patients were equally divided into two groups. Group I had a pre-vancomycin protocol among 175 cases, and 175 cases of Group II received the vancomycin protocol. Postoperative septic arthritis was a likely outcome in both groups. Combining clinical findings with cytological examination of joint aspiration (cell count >50,000/μL and >90% neutrophils), a diagnosis of likely septic arthritis was reached. A Fisher's exact test was used for statistical analysis. We fixed the significance level at p<0.05. Results: There were a majority of 240 (68.6%) male and 110 (31.4%) female among all cases. Included cases had a mean age of 27.18 ± 11.58 years and had a mean BMI of 26.12 ± 8.38 kg/m2. Post-operatively, the frequency of septic arthritis was only found in group I among 7 (17.1%) cases, and no cases were found in group II. Among 7 cases of septic arthritis in group I, 4 cases had Staphylococcus epidermidis, and no organisms were isolated in 3 cases. Conclusions: It was concluded that presoaking the grafts in vancomycin for primary ACL repair decreased the likelihood of postoperative septic arthritis compared to not soaking them.